Sorogan and How to Use it in Teaching English - M. Alimul Huda; Feri Huda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
One of the obstacles in learning English is ignorance in the use of distinguishing functions of part of speech, verbal and nominal sentences, and tenses. This article describes the application of the Sorogan method in learning English for beginners, where for many years this method is still being used in learning Arabic in Islamic boarding schools in Indonesia. Descriptive design works to explain the use of this method. The population and samples were obtained from students majoring in English Education Department of University PGRI Adi Buana Campus Blitar. The results of the questionnaire display that students feel engaged in the implementation of Sorogan.